Gambaran faktor yang mempengaruhi pemilihan kontrasepsi suntik DMPA di Puskesmas Sleman Tahun 2015 - Hastika Ulfatu Nikmah; Anita Rahmawati; Munica Rita Hernayanti (Jurnal Kesehatan Ibu dan Anak, 2016)
Background: Data Indonesian Health Ministry shows that there are 8,500,247 new family planning participants with 48.56%using injectable contraceptives. The percentage of participants KBsuntik active in the province is the highest ie 46.01%, inPuskesmas Sleman acceptors injecting 48.5%). Acceptors who choose injeciables because of several factors. Objective: Todetermine the factors that influence the selection of picture injectable contraceptive DMPA in Puskesmas Sleman 2015.Methods: descriptive study with cross sectional design. Location of the study in Puskesmas Sleman with research subjectsthroughout the injectable DMPA acceptors who visit the Puskesmas Sleman with the number of respondents 35 people.Results: Factors that influencethe selectionof injectable contraceptive DMPAinPuskesmas Sleman 2015 include the ageofthe respondent is a risk of cancer were age> 35 years a number of 31.43, the majority of respondents' education is junior(48.57%), did not work/IRT as much as 54.29%, parity mutipara much 51.43%>, and have sufficient knowledge as much as65.71%). Conclusion: Overview of factors that influence the selection of injectable contraceptive DMPA in PuskesmasSleman, the majority aged S35 years (less a risk of cancer), junior high school education, the majority of respondents in thisstudy is not working /IRT, having morethanone child,and have sufficient knowledge about the DMPA injections.